Advances in Research at Synthesis Process Optimization and Quality Standard Improvement of O-desmethylvenlafaxine Succinate - Yang, Shiwei; Chen, Shiyun; Wang, Cheng; Zhang, Shibo; Li, Shuaifei; Yuan, Xinsong; Peng, Fuyun; He, Yong (Frontiers in Chemistry, 2022)
We herein describe an optimal approach for the efficient synthesis of O-desmethylvenlafaxine succinate monohydrate (DVS) with high yield and high purity through 5-step reactions, including benzyl protection of the phenolic hydroxyl group, cyclohexanone condensation, deprotection, cyano reduction, dimethylation, and succinic acid salt formation from p-hydroxybenzene acetonitrile as a starting material. 4-Benzyloxyphenylacetonitrile (Intermediate I) was prepared by the hydroxyl protection of the bromide benzyl-p-hydroxyphenylacetonitrile catalyzed by potassium carbonate with 99.83% purity and 98.92% yields. The 1, 2-nucleophilic addition of intermediate I to cyclohexanone promoted by sodium hydroxide with the homogeneous catalyst (n-Bu)4N+Br− to the preparation of 1-[Cyano(4-benzyloxyphenyl)methyl]cyclohexanol (Intermediate II) was obtained by 99.13% purity and 99.71% yields. Cyclohexanone residues and benzyl bromide residues were trace, and tetrabutylammonium bromide residues were UNDER 0.7 ppm, which further improves the residual standards for genotoxic impurities (GIs). 1-[2-amino-1-(4-hydroxyphenyl)ethyl]cyclohexanol hydrochloride (Intermediate III) was prepared by 10% palladium-carbon under 2.0 MPa up to 98.32% purity and 94.20% yields. O-desmethylvenlafaxine (ODV) was synthesized by dimethylation of intermediate III with 37% formaldehyde solution and 85% formic acid solution. The highest purity was up to 99.20% and the yield was up to 84.77%. O-desmethylvenlafaxine succinate monohydrate (DVS) was formed from succinic acid and O-desmethylvenlafaxine (ODV) and crystallized in a mixed solvent of acetone and water (3:1) to obtain 99.92% purity and 90.27% yields. The 5-step total yields of desvenlafaxine succinate monohydrate is 71.09%, and its crystal form has characteristic peaks at 5, 10, 21, and 26 min by XRD powder diffraction, which is consistent with the crystalline form I. Compared with conventional synthesis strategy, we revealed a novel and green process with a high total yield, high atomic economy, low environmental pollution, high operational safety, and high residual standards for genotoxic impurities (GIs), which improves drug safety.